Rotordynamic Faults: Recent advances in diagnosis and prognosis - Walker, Ryan B.; Perinpanayagam, Suresh; Jennions, Ian K. (Hindawi Publishing Corporation, 2013)
Diagnosis and condition monitoring in rotating machinery has been a subject of intense research for the last century. Recent developments indicate the drive towards integration of diagnosis and prognosis algorithms in future Integrated Vehicle Health Management (IVHM) systems. With this in mind, this paper concentrates on highlighting some of the latest research in common faults in rotating machines. Eight key faults have been described; the selected faults include unbalance, misalignment, rub/looseness, fluid-induced instability, bearing failure, shaft cracks, blade cracks and shaft bow. Each of these faults has been detailed with regards to sensors, fault identification techniques, localization, prognosis and modelling. The intent of the paper is to highlight the latest technologies pioneering the drive towards next generation IVHM systems for rotating machinery.